Problems Arising from Legal Legislation in Disablement/Disability Rate Calculation - Turla, Ahmet; Dilber, Ali İhsan; Tecir, Umut; Aydın, Berna (The Bulletin of Legal Medicine, 2024)
Every year, many people in our country lose their health due to traffic accidents, work accidents, and occupational diseases, and they continue the rest of their lives with varying degrees of damage. In terms of compensation law, various tables included in legal regulations are used to determine the extent of the damage. Which regulation will be applied when determining the disability rate also causes confusion in judicial decisions due to frequently changing legislation in recent years. Our forensic medicine polyclinic has been responding to a large number of disability rate requests for many years. The aim of this text is to discuss the some problems encountered in practice within the framework of the current disability legislation and to make suggestions about some situations that are not included in the legislation or are inadequate. Having legal regulations that are clear, understandable and do not require much interpretation when calculating disability rates is an important factor that facilitates the work of experts who prepare reports on disability. At the same time, the table of sequelae included in the legislation should be update by discussing them at regular intervals with experts in the field, in line with changing and developing medical information.
Keywords: Disability; expert witness; dominant hand; leg length; amputation; epilepsy